Monoclonal and polyclonal antibodies production - preparation of potent biorecognition element - Pohanka, Miroslav (Journal of Applied Biomedicine, 2009)
Antibodies are macromolecular structures with a high affinity to a molecule called the antigen. Though the natural aim of antibodies is the protection of the body from pathogens, they have been found to play a useful part in a number of specific treatments and diagnoses. This wider role for antibodies extends to assays where antibodies provide a recognition capability improving available physical methods. Photometrical methods such as ELISA or flow cytometry and electrochemical, optical or piezoelectric immunosensors (biosensors) are typical examples. The present review summarizes facts about the parameters and the production of antibodies. The structure of immunoglobulins, and the production and purification of monoclonal and polyclonal antibodies are described in four chapters. The review was written in order to collect the available knowledge on antibodies into one study improving orientation in this field for anyone wanting to construct immunoassays.
Keywords: financování organizované; Immunoassay; Enzyme-Linked Immunosorbent Assay; Chemical Warfare Agents; biologické bojové látky; Adjuvants, Immunologic; Antibody Formation; Antibodies, Monoclonal; lidé; chemické bojové látky; tvorba protilátek; Antibodies; Biosensing Techniques; laboratorní zvířata; Immunoglobulins; Financing, Organized; Biological Warfare Agents; Animals, Laboratory; ELISA; imunoanalýza; biosenzitivní techniky; monoklonální protilátky; imunoglobuliny; adjuvancia imunologická; protilátky; Humans